Au nanoparticles deposited on ultrathin two-dimensional covalent organic framework nanosheets for in vitro and intracellular sensing. Issue 14 (26th March 2020) - Tian, Yuanyuan; Lu, Qipeng; Guo, Xixi; Wang, Siyu; Gao, Yu; Wang, Lianhui
Abstract : A novel fluorescence platform based on hybrid nanosheets (Au NPs/COF NSs) for sensing and imaging. Abstract : A novel composite nanomaterial is prepared by growing small Au nanoparticles on two-dimensional covalent organic framework nanosheets (Au NPs/COF NSs). The synthesized hybrid nanosheets are used as a new platform for multiplexed detection of hepatitis A virus DNA (HAV) and hepatitis B virus DNA (HBV). Additionally, this sensing platform based on Au NPs/COF NSs can be used as a candidate for monitoring the distribution of potassium ions (K + ) and the intracellular K + level in living cells. Accordingly, the sensing systems based on hybrid Au NPs/COF NSs have shown great potential for the investigation of biomolecules and related biological applications.